2014
DOI: 10.1002/pola.27091
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of polyhydroxyurethane bearing silicone backbone

Abstract: Polyhydroxyurethane bearing silicone backbone was prepared by polyaddition of silicone diamines with a bifunctional five-membered cyclic carbonate prepared from the corresponding diepoxide and CO 2 . Polymerization in propylene glycol methyl ether acetate proceeded smoothly, and polymers could be obtained in high yields under appropriate conditions. The introduced silicone moieties improved the hydrophobicity and lowered the glass transition temperature keeping thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…Especially, NIPUs prepared from renewable natural resources have been described extensively for their low cost, biocompatibility and possible biodegradability [12][13][14][15][16][17][18]. Recently, for the purpose of improving the properties of NIPUs, several modifications have been exploited [19][20][21][22][23].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Especially, NIPUs prepared from renewable natural resources have been described extensively for their low cost, biocompatibility and possible biodegradability [12][13][14][15][16][17][18]. Recently, for the purpose of improving the properties of NIPUs, several modifications have been exploited [19][20][21][22][23].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Especially, ve-membered cyclic carbonates can be derived from epoxides and CO 2 under mild conditions; therefore, the studies on PHUs are interesting in the eld of green chemistry. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Especially, ve-membered cyclic carbonates can be derived from epoxides and CO 2 under mild conditions; therefore, the studies on PHUs are interesting in the eld of green chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Especially, ve-membered cyclic carbonates can be derived from epoxides and CO 2 under mild conditions; therefore, the studies on PHUs are interesting in the eld of green chemistry. It has been reported that silicone-conjugated PHUs show lower glass transition temperatures and good water repelling properties, 3 and network gels of PHUs are obtainable by reactions with aluminum or titanium alkoxides 10 or by the free-radical polymerization of PHUs bearing methacryl groups. PHUs are also interesting concerning the introduction of functionalities by the use of functional diamines or by chemical modications via their hydroxyl side chains.…”
Section: Introductionmentioning
confidence: 99%
“…PHUs can be functionalized by the use of functional diamines or by chemical modifications via their hydroxyl side chains. Nowadays it has been reported that silicone-conjugated PHUs show lower glass transition temperatures and well water repelling properties (Ochiai, 2014) and networked PHU gels are obtainable by the reaction with metal alkoxides (Kihara, 1996) or by the free-radical polymerization of methacryl groups modified in their side chains . In addition, urethane linkages of PHUs can be degraded at alkaline conditions and further shows biodegradability, thus, PHUs are one of promising candidates for versatile materials based on biocompatibility and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, five-membered cyclic carbonates (5-CCs) can be derived from epoxides and CO 2 under mild conditions (Fleischer, 2013;Sheng, 2015) and therefore, numerous 5-CCs-derived PHUs have been synthesized using bisphenol A (Ochiai, 2014;Lambeth, 2013;Kihara, 1996) and bio-based polyols (Kathalewar, 2015;Annunziata, 2014;Guillaume, 2013;Guillaume, 2011) as starting materials. PHUs can be functionalized by the use of functional diamines or by chemical modifications via their hydroxyl side chains.…”
Section: Introductionmentioning
confidence: 99%